A graphene aerogel-based electroswing adsorption method

By inlaiding copper sheets in quartz tubes and utilizing the electrochemical properties of graphene aerogels, CO2 adsorption and desorption are quickly realized, which solves the problem of long heating time of the temperature variable adsorption method, reduces energy consumption and improves the CO2 removal rate.

CN117839632BActive Publication Date: 2024-12-17ZHEJIANG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410163156.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-05
Publication Date
2024-12-17
Estimated Expiration
2044-02-05

AI Technical Summary

Technical Problem

The existing temperature variable adsorption method has a long heating and cooling time, a long cycle time, and high energy consumption when used with high current, making it difficult to quickly and effectively realize CO2 desorption.

Method used

Prepare with graphene aerogel and set with copper sheets in quartz tubes. The adsorbent can quickly reach the desorption temperature by applying heating through current. Combined with the efficient modification of graphene aerogel and impregnation of active components, it can achieve rapid CO2 adsorption and desorption. Attached.

Benefits of technology

The efficient CO2 adsorption and desorption of graphene aerogels is achieved, the space utilization rate reaches 100%, the desorption temperature is reached in a short time, the energy consumption is reduced, the CO2 removal rate is high, and the concentration of CO2 products directly desorbed by electric thermal desorption is close to 100%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117839632B_ABST
    Figure CN117839632B_ABST
Patent Text Reader

Abstract

The present invention discloses a graphene aerogel-based electrostatic adsorption method, which includes three parts: graphene aerogel preparation, active component impregnation and electrostatic adsorption. A quartz tube is used to make an adsorption column, and copper sheets are embedded inside the two ends of the adsorption column and wires are led out to facilitate the connection of electrodes. The preparation of graphene aerogel, active component impregnation and electrostatic adsorption are completed in the same adsorption column. The present invention can achieve 100% space utilization of the adsorption column by placing a graphene film in the adsorption column to foam it into foam and fill the adsorption column. The adsorption tower uses copper sheets embedded inside the two ends and copper wires are led out to achieve the purpose of applying current. Only a small current is needed to make the graphene aerogel reach the desorption temperature in a short time, thereby quickly desorbing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of gas separation, and in particular to an electroswing adsorption method based on graphene aerogel. Background Art

[0002] Since the Industrial Revolution, the content of greenhouse gases in the atmosphere has risen sharply due to the burning of fossil fuels. The problem of global warming has reached a point where it cannot be delayed. Various measures must be taken to reduce greenhouse gas emissions. CO2 is the main component of greenhouse gases. Therefore, reducing CO2 emissions is imperative. Carbon capture, utilization and storage technology plays a key role in carbon emission reduction. In recent decades, various adsorbents have been developed to achieve high adsorption capacity and high adsorption selectivity, and to a certain extent, energy consumption has also been reduced.

[0003] Solid adsorption can be divided into pressure swing adsorption and temperature swing adsorption according to its CO2 regeneration method. The temperature swing adsorption method is to adjust the temperature so that the adsorbent adsorbs under low temperature conditions and desorbs under high temperature conditions. Due to the heat transfer rate of the system, temperature swing adsorption is often limited, the heating and cooling time is very long, and the cycle time of temperature swing adsorption is also relatively long. Therefore, fast and effective heating methods are one of the important research directions of temperature swing adsorption. The electrostatic adsorption method is a special temperature swing adsorption method. Its main feature is to regenerate the adsorbent by generating heat energy through the Joule effect of electric current. By adjusting the current size, the temperature required for adsorbent desorption can be achieved. Compared with the temperature swing adsorption method, the electrostatic adsorption method can reach a stable temperature faster, thereby reducing the desorption time. The currently commonly used current is 3-6V. A higher current can quickly heat the adsorbent to the desorption temperature, but the corresponding energy consumption is also higher. Summary of the invention

[0004] In view of the characteristics of the prior art, the present invention provides a graphene aerogel-based electroswing adsorption method, comprising:

[0005] The electrostatic adsorption process includes three parts: graphene aerogel preparation, active component impregnation and electrostatic adsorption. A quartz tube is used to make an adsorption column with an inner diameter of 2-6 mm and a length of 30-50 mm (preferably an inner diameter of 4 mm and a length of 40 mm). Copper sheets are embedded inside the two ends of the adsorption column and wires are led out to facilitate the connection of electrodes.

[0006] (1) According to the size of the adsorption column, a graphene film of appropriate size is selected and placed in the adsorption column, and then immersed in a hydrazine hydrate solution to allow the graphene film to foam and fill the entire adsorption column, and then immersed in excess anhydrous ethanol and n-hexane solution to replace the hydrazine hydrate in the foam, and dried in a forced air oven at 60-80°C for 8-10 hours. Then, it is placed in a tubular furnace to complete thermal reduction and argon plasma treatment.

[0007] (2) The adsorption column filled with graphene aerogel obtained in step 1 and the excess active component (immersed adsorption column) are placed in a reaction kettle, heated in an oven at 80 to 100° C. for 10 to 12 h, washed with anhydrous ethanol for 20 to 40 min, and dried in a forced air oven at 60 to 90° C. for 8 to 12 h.

[0008] (3) The adsorption column filled with active component modified graphene aerogel obtained in step 2 is installed on the adsorption penetration device, the positive and negative electrodes are connected to the wires on both sides of the adsorption column, 10-100 mL / min of argon gas is introduced, and a current of 0.4-1 A is applied to the adsorption column using an electrochemical workstation. After observing that the residual CO2 in the pipeline is basically removed through the gas chromatograph connected to the gas outlet of the adsorption column, the current is stopped. After the temperature of the adsorption column drops to room temperature, the argon gas is turned off, and a CO2 / N2 mixed gas with a CO2 concentration of 400 ppm is introduced for CO2 adsorption. After the CO2 adsorption is observed to be saturated on the gas chromatograph, the mixed gas is turned off, 10-100 mL / min of argon gas is introduced, and a current of 0.4-1 A is applied for CO2 desorption.

[0009] Furthermore, in step (1), the concentration of the hydrazine hydrate solution is 30-60%, and the foaming time is 1-3 hours.

[0010] Furthermore, the replacement step in step (1) is to soak in an excess of anhydrous ethanol solution for 2 to 5 hours, and then replace with a new anhydrous ethanol solution and repeat three times; soak in an excess of n-hexane solution for 2 to 5 hours, and then replace with a new n-hexane solution and repeat three times;

[0011] Furthermore, the thermal reduction and argon plasma treatment in step (1) are as follows: in an argon atmosphere, the oxygen in the tube furnace is removed by vacuuming 2 to 3 times, the temperature is raised to 600 to 800 degrees Celsius at a heating rate of 10 to 15°C / min, maintained for 4 to 7 hours, and the argon flow rate is 20 to 100 mL / min. Then, the vacuum pump is turned on, and argon plasma treatment is performed for 20 to 60 minutes under low pressure conditions, the plasma intensity is 100 to 200 W, and then it is naturally cooled to room temperature.

[0012] Furthermore, the active component in step (2) is tetraethylenepentamine TEPA, pentaethylenehexamine PEHA, triethylenetetramine-2-methylimidazole salt [TETAH][2-MI].

[0013] Furthermore, the gas flow rate of the CO2 / N2 mixed gas in step (3) is 0.01 to 1 m / s.

[0014] Compared with the prior art, the present invention has the following advantages:

[0015] The present invention realizes the preparation of graphene aerogel, impregnation of active components and electrostatic adsorption in the same adsorption column. By placing the graphene film in the adsorption column and foaming it into foam to fill the adsorption column, the space utilization rate of the adsorption column can be 100%. The adsorption tower adopts copper sheets embedded in the two ends and copper wires to achieve the purpose of applying current. Only a small current is needed to make the graphene aerogel reach the desorption temperature in a short time, so as to desorb quickly. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Schematic diagram of copper sheet embedded inside the adsorption column.

[0017] Figure 2 Figure 2 is a diagram of the electroswing adsorption process coupled with renewable energy. DETAILED DESCRIPTION

[0018] The present invention will be further described below in conjunction with specific embodiments. The illustrative embodiments and descriptions of the present invention are used to explain the present invention but are not intended to limit the present invention.

[0019] like Figure 1 As shown in the figure, the structure of the adsorption column is inlaid with copper sheets. Figure 2 Shown is the electroswing adsorption process coupled with renewable energy.

[0020] The graphene film was prepared by spreading 8 mg / g of graphene oxide aqueous dispersion (Hangzhou Gaoxin Technology Co., Ltd., model GO-1 / g) on ​​a plastic culture dish with a thickness of 5 mm and drying it in a forced air oven at 60°C for 6 h.

[0021] Example 1

[0022] A graphene aerogel-based electroswing adsorption process, the details of which are as follows:

[0023] (1) Take a 4×40 mm graphene film and place it in an adsorption column, soak it in a hydrazine hydrate solution with a hydrazine mass fraction of 40% for 2 hours, soak it in an excess of anhydrous ethanol solution for 3 hours, and then replace it with a new anhydrous ethanol solution for three times, soak it in an excess of n-hexane solution for 3 hours, and then replace it with a new n-hexane solution for three times, and dry it in a 60°C forced air oven for 8 hours. Place it in a tube furnace for thermal reduction and argon plasma treatment: in an argon atmosphere, vacuum the tube furnace three times to remove oxygen, heat it to 700 degrees Celsius at a rate of 10°C / min, maintain it for 5 hours, and the argon flow rate is 20mL / min. Then turn on the vacuum pump and perform argon plasma treatment for 30 minutes under low pressure conditions. The plasma intensity is 200W, and then it naturally drops to room temperature 25°C to obtain an adsorption column filled with graphene aerogel.

[0024] (2) The adsorption column filled with graphene aerogel obtained in step 1 and excess TEPA (immersed adsorption column) were placed in a reactor, heated in an oven at 90° C. for 10 h, washed with anhydrous ethanol for 20 min, and dried in a forced air oven at 80° C. for 10 h.

[0025] (3) The adsorption column filled with active component modified graphene aerogel obtained in step 2 is installed on the adsorption penetration device, the positive and negative electrodes are connected to the wires on both sides of the adsorption column, 10 mL / min of argon gas is introduced, and a current of 0.6 A is applied to the adsorption column using an electrochemical workstation. After observing that the residual CO2 in the pipeline is basically removed through the gas chromatograph connected to the gas outlet of the adsorption column, the current is stopped, and after the temperature of the adsorption column drops to room temperature, the argon gas is turned off, and a mixed gas of CO2 / N2 with a CO2 concentration of 400 ppm at a flow rate of 1 m / s is introduced for CO2 adsorption. After the CO2 adsorption saturation is observed on the gas chromatograph, the mixed gas is turned off, 10 mL / min of argon gas is introduced, and a current of 0.6 A is applied for CO2 desorption.

[0026] The 4×40 mm graphene film prepared in this embodiment can fill the adsorption column after foaming in hydrazine hydrate solution for 2 hours, and the space utilization rate of the adsorption column is 100%. The CO2 / N2 mixed gas with a flow rate of 1 m / s and a concentration of 400 ppm is introduced to make the TEPA-modified graphene aerogel adsorb CO2, and the adsorption amount is 2.5 mmol / g. After the adsorption is completed, the desorption temperature of 80°C can be reached in a short time by applying a current of 0.6A. The energy consumption is about 3.2 GJ / t CO2 when desorption is 95%. The concentration of CO2 product directly desorbed by electrothermal desorption is 99.8%, and the CO2 removal rate is 90%.

[0027] Example 2

[0028] A graphene aerogel-based electroswing adsorption process, the details of which are as follows:

[0029] (1) Take a 4×40 mm graphene film and place it in an adsorption column, soak it in a hydrazine hydrate solution with a hydrazine mass fraction of 50% for 90 minutes, soak it in an excess of anhydrous ethanol solution for 3 hours, and repeat it three times with a new anhydrous ethanol solution, soak it in an excess of n-hexane solution for 3 hours, and repeat it three times with a new n-hexane solution, and dry it in a 60°C forced air oven for 10 hours. Place it in a tube furnace for thermal reduction and argon plasma treatment: in an argon atmosphere, vacuumize the tube furnace three times to remove oxygen, raise the temperature to 700 degrees Celsius at a rate of 10°C / min, maintain it for 5 hours, and the argon flow rate is 20mL / min. Then turn on the vacuum pump and perform argon plasma treatment for 30 minutes under low pressure conditions with a plasma intensity of 200W, and then naturally cool it to room temperature.

[0030] (2) The adsorption column filled with graphene aerogel obtained in step 1 and excess [TETAH][2-MI] (immersed adsorption column) were placed in a reaction kettle, heated in an oven at 90° C. for 10 h, washed with anhydrous ethanol for 30 min, and dried in a forced air oven at 80° C. for 10 h.

[0031] (3) The adsorption column filled with active component modified graphene aerogel obtained in step 2 is installed on the adsorption penetration device, the positive and negative electrodes are connected to the wires on both sides of the adsorption column, 10 mL / min of argon gas is introduced, and a current of 0.6 A is applied to the adsorption column using an electrochemical workstation. After observing that the residual CO2 in the pipeline is basically removed through the gas chromatograph connected to the gas outlet of the adsorption column, the current is stopped, and after the temperature of the adsorption column drops to room temperature, the argon gas is turned off, and a mixed gas of CO2 / N2 with a CO2 concentration of 400 ppm at a flow rate of 1 m / s is introduced for CO2 adsorption. After the CO2 adsorption saturation is observed on the gas chromatograph, the mixed gas is turned off, 10 mL / min of argon gas is introduced, and a current of 0.6 A is applied for CO2 desorption.

[0032] The 4×40 mm graphene film prepared in this embodiment can fill the adsorption column after foaming in the hydrazine hydrate solution for 90 minutes, and the space utilization rate of the adsorption column is 100%. The mixed gas of CO2 / N2 with a CO2 concentration of 400ppm at a flow rate of 1m / s is introduced to make the graphene aerogel modified with [TETAH][2-MI] adsorb CO2, and the adsorption amount is 1.4mmol / g. After the adsorption is completed, the desorption temperature of 80°C can be reached in a short time by applying a current of 0.6A. The energy consumption is about 3.8GJ / t CO2 when desorption is 95%. The concentration of CO2 product directly desorbed by electrothermal desorption is 99.5%, and the CO2 removal rate is 88%.

Claims

1. A graphene aerogel-based electroswing adsorption method, characterized in that: The following steps are involved: (1) A quartz tube is used to make an adsorption column, copper sheets are embedded inside the two ends of the adsorption column and wires are led out, a graphene film is selected according to the size of the adsorption column and placed in the adsorption column, and the graphene film is soaked in a hydrazine hydrate solution to make the graphene film foam and fill the entire adsorption column, and then the hydrazine hydrate in the foam is replaced by soaking, first soaking in anhydrous ethanol, and then soaking in n-hexane, taking out the adsorption column and drying it, and then placing it in a tubular furnace to complete thermal reduction and argon plasma treatment, so as to obtain an adsorption column filled with graphene aerogel; (2) placing the adsorption column filled with graphene aerogel obtained in step (1) and the active component into a reaction kettle, wherein the active component is tetraethylenepentamine, pentaethylenehexamine or triethylenetetramine-2-methylimidazolium salt, heating in an oven at 80-100° C. for 10-12 h, washing and drying to obtain an adsorption column filled with active component-modified graphene aerogel; (3) installing the adsorption column filled with active component-modified graphene aerogel obtained in step (2) on an adsorption penetration device, connecting the positive and negative electrodes to the wires on both sides of the adsorption column, introducing argon gas at a rate of 10 to 100 mL / min, applying a current of 0.4 to 1 A to the adsorption column, and stopping applying the current after observing that the residual CO2 in the pipeline is basically removed through a gas chromatograph connected to the gas outlet of the adsorption column. After the temperature of the adsorption column is cooled down, the argon gas is turned off, and a mixed gas containing CO2 is introduced to adsorb CO2; After CO2 adsorption saturation was observed on the gas chromatograph, the mixed gas was turned off, argon gas was introduced at a rate of 10-100 mL / min, and a current of 0.4-1 A was applied for CO2 desorption.

2. The graphene aerogel-based electroswing adsorption method according to claim 1, characterized in that: In step (1), the size of the adsorption column is: an inner diameter of 2-6 mm and a length of 30-50 mm.

3. The graphene aerogel-based electroswing adsorption method according to claim 1, characterized in that: In step (1), the mass fraction of hydrazine in the hydrazine hydrate solution is 30-60%, and the foaming time of immersion in the hydrazine hydrate solution is 1-3 hours.

4. The graphene aerogel-based electroswing adsorption method according to claim 1, characterized in that: In step (1), the sample is first immersed in anhydrous ethanol for three times, each time for 2 to 5 hours, and a new anhydrous ethanol is replaced each time; Then soak in n-hexane three times, each time for 2 to 5 hours, and replace new n-hexane each time.

5. The graphene aerogel-based electroswing adsorption method according to claim 1, characterized in that: In step (1), the drying conditions are: drying in a forced air oven at 60-80°C for 8-10 hours.

6. The graphene aerogel-based electroswing adsorption method according to claim 1, characterized in that: In step (1), the thermal reduction and argon plasma treatment are performed in a tube furnace and specifically include: In an argon atmosphere, remove oxygen from the tube furnace by vacuuming 2 to 3 times, raise the temperature to 600 to 800 degrees Celsius at a heating rate of 10 to 15 degrees Celsius / min, maintain for 4 to 7 hours, and the argon flow rate is 20 to 100 mL / min. Then turn on the vacuum pump and perform argon plasma treatment for 20 to 60 minutes under low pressure conditions with a plasma intensity of 100 to 200 W, followed by natural cooling.

7. The graphene aerogel-based electroswing adsorption method according to claim 1, characterized in that: In step (2), the active component is immersed in the adsorption column filled with graphene aerogel.

8. The graphene aerogel-based electroswing adsorption method according to claim 1, characterized in that: In step (2), the washing conditions are: washing with anhydrous ethanol for 20 to 40 minutes.

9. The graphene aerogel-based electroswing adsorption method according to claim 1, characterized in that: In step (2), the drying conditions are: drying in a forced air oven at 60-90°C for 8-12 hours.

Citation Information

Patent Citations

  • Materials, systems, and methods for co2 capture and conversion

    US20210069637A1

  • Graphene and graphene oxide aerogels / xerogels for co2 capture

    WO2013132259A1